ILAE classification and definition of epilepsy syndromes with onset in neonates and infants: Position statement by the ILAE Task Force on Nosology and Definitions. Issue 6 (3rd May 2022) - Zuberi, Sameer M.; Wirrell, Elaine; Yozawitz, Elissa; Wilmshurst, Jo M.; Specchio, Nicola; Riney, Kate; Pressler, Ronit; Auvin, Stephane; Samia, Pauline; Hirsch, Edouard; Galicchio, Santiago; Triki, Chahnez; et al.
Abstract: The International League Against Epilepsy (ILAE) Task Force on Nosology and Definitions proposes a classification and definition of epilepsy syndromes in the neonate and infant with seizure onset up to 2 years of age. The incidence of epilepsy is high in this age group and epilepsy is frequently associated with significant comorbidities and mortality. The licensing of syndrome specific antiseizure medications following randomized controlled trials and the development of precision, gene‐related therapies are two of the drivers defining the electroclinical phenotypes of syndromes with onset in infancy. The principal aim of this proposal, consistent with the 2017 ILAE Classification of the Epilepsies, is to support epilepsy diagnosis and emphasize the importance of classifying epilepsy in an individual both by syndrome and etiology. For each syndrome, we report epidemiology, clinical course, seizure types, electroencephalography (EEG), neuroimaging, genetics, and differential diagnosis. Syndromes are separated into self‐limited syndromes, where there is likely to be spontaneous remission and developmental and epileptic encephalopathies, diseases where there is developmental impairment related to both the underlying etiology independent of epileptiform activity and the epileptic encephalopathy. The emerging class of etiology‐specific epilepsy syndromes, where there is a specific etiology for the epilepsy that is associated with a clearly defined, relatively uniform, and distinct clinical phenotype in most affected individuals as well as consistent EEG, neuroimaging, and/or genetic correlates, is presented. The number of etiology‐defined syndromes will continue to increase, and these newly described syndromes will in time be incorporated into this classification. The tables summarize mandatory features, cautionary alerts, and exclusionary features for the common syndromes. Guidance is given on the criteria for syndrome diagnosis in resource‐limited regions where laboratory confirmation, including EEG, MRI, and genetic testing, might not be available.